Using a Tip Characterizer to Investigate Microprobe Silicon Tip Geometry Variation in Roughness Measurements - Min Xu; Ziqi Zhou; Thomas Ahbe; Erwin Peiner; Uwe Brand (Sensors, 2022)
Given their superior dynamics, microprobes represent promising probe candidates for high-speed roughness measurement applications. Their disadvantage, however, lies in the fact that the volume of the microprobe’s silicon tip decreases dramatically during roughness measurement, and the unstable tip geometry leads to an increase in measurement uncertainty. To investigate the factors that influence tip geometry variation during roughness measurement, a rectangular-shaped tip characterizer was employed to characterize the tip geometry, and a method for reconstructing the tip geometry from the measured profile was introduced. Experiments were conducted to explore the ways in which the tip geometry is influenced by tip wear, probing force, and the relative movement of the tip with respect to the sample. The results indicate that tip fracture and not tip wear is the main reason for tip volume loss, and that the lateral dynamic load on the tip during scanning mode is responsible for more tip fracture than are other factors.